Increased expression of high mobility group box 1 (HMGB1) is associated with an elevated level of the antiapoptotic c‐IAP2 protein in human colon carcinomas - Völp, K (BMJ Group, 2006)
BACKGROUND: High mobility group box 1 (HMGB1) is a non‐histone chromosomal protein implicated in a variety of biologically important processes, including transcription, DNA repair, V(D)J recombination, differentiation, and development. Overexpression of HMGB1 inhibits apoptosis, arguing that the molecule may act as an antiapoptotic oncoprotein. Indeed, increased expression of HMGB1 has been reported for several different tumour types. In this study, we analysed human colon carcinoma for HMGB1 as well as for c‐IAP2 expression levels. c‐IAP2 is an antiapoptotic protein which may be upregulated as a consequence of nuclear factor κB (NFκB) activation via HMGB1. METHODS: A comparative genomic hybridisation (CGH) database comprising 1645 cases from different human tumour types was screened to detect cytogenetic changes at the HMGB1 locus. Immunohistochemical staining of human colon tissue microarrays and tumour biopsies, as well as western blot analysis of tumour lysates, were performed to detect elevated HMGB1 and c‐IAP2 expression in colon carcinomas. The antiapoptotic potential of HMGB1 was analysed by measuring caspase activities, and luciferase reporter assays and quantitative polymerase chain reaction analysis were employed to confirm NFκB activation and c‐IAP2 mRNA upregulation on HMGB1 overexpression. RESULTS: According to CGH analysis, the genomic locus containing the HMGB1 gene was overrepresented in one third (35/96) of colon cancers. Correspondingly, HMGB1 protein levels were significantly elevated in 90% of the 60 colon carcinomas tested compared with corresponding normal tissues evaluable from the same patients. HMGB1 increased NFκB activity and led to co‐overexpression of the antiapoptotic NFκB target gene product c‐IAP2 in vitro. Furthermore, increased HMGB1 levels correlated with enhanced amounts of c‐IAP2 in colon tumours analysed by us. Finally, we demonstrated that HMGB1 overexpression suppressed caspase‐9 and caspase‐3 activity, suggesting that HMGB1 interferes with the apoptotic machinery at the level of apoptosomal caspase‐9 activation. CONCLUSIONS: We identified in vitro a molecular pathway triggered by HMGB1 to inhibit apoptosis via c‐IAP2 induction. Our data indicate a strong correlation between upregulation of the apoptosis repressing HMGB1 and c‐IAP2 proteins in the pathogenesis of colon carcinoma.